Brain metastasis from differentiated thyroid carcinoma responding to radioiodine therapy - Leo Hashimoto; Shiro Watanabe; Mungunkhuyag Majigsuren; Kenji Hirata; Junki Takenaka; Rina Kimura; Hiroshi Ishii; Kohsuke Kudo (Asia Oceania Journal of Nuclear Medicine and Biology, 2025)
Brain metastasis (BM) occurs only in about 1% of differentiated thyroid carcinoma (DTC) cases. Although DTC generally has a good prognosis, once BM develops, the mortality rate significantly increases up to 78%. BM is usually treated by surgical resection or external radiotherapy, whereas radioactive iodine therapy (RAIT) using I-131 is much less often chosen because BM often shows poor uptake of I-131. In addition, even in case I-131 accumulates in the BM, RAIT could cause adverse effects such as brain hemorrhage and cerebral edema. We present a case of BM from DTC that showed response to I-131 therapy with no severe adverse effects. The brain lesion was very small and asymptomatic, and was only found after a post-therapy I-131 scintigraphy. There are a few case reports where BM was cured by RAIT with little to no side effects. We theorize that BM that is small in size, asymptomatic and show I-131 accumulation could be successfully treated with RAIT.